Effects of processing on the recovery of food allergens from a model dark chocolate matrix. (1st February 2015) - Khuda, Sefat E; Jackson, Lauren S.; Fu, Tong-Jen; Williams, Kristina M.
Highlights: We evaluate recovery of food allergens from a processed dark chocolate matrix. We compare extractability of major allergenic proteins with different buffers. Immunodetection of allergenic proteins depends on the specificity of antibodies. Abstract: To alleviate the risk to allergic consumers, it is crucial to improve factors affecting the detection of food allergens in processed chocolate products. This study evaluated processing effects on (1) recovery of peanut, egg, and milk allergens using five different extraction buffers, and (2) identification of specific allergenic proteins from extracts of incurred chocolate using allergen-specific antibodies and human allergic sera. Immunochemical staining with polyclonal antibodies showed that the addition of detergent or reducing agent improved extraction efficiency of peanut proteins, but not of egg and milk proteins. Tempering decreased antibody binding regardless of extractant. Detection of IgE-reactive peanut, egg, and milk allergens was differentially affected by tempering and extractant. Detection problems associated with matrix and processing effects may be overcome by the choice of extraction buffer and detecting antibody.